Hubungan Kemampuan Pemecahan Masalah Matematika dengan Gaya Belajar Siswa - Ramadoni Ramadoni; Harnof Dimas (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The purpose of this study was to determine the relationship between mathematical problem solving abilities and students' learning styles. Student learning styles are important in the learning process and understanding student learning styles. Recognizing student learning styles will make it easier to choose appropriate learning activities and make it easier for students to receive information. This type of research is quantitative research. The instruments used are test questions and questionnaires. The sample in this study were class XI students of SMA Negeri 1 Suliki with a total of 20 students. The results of the research are in the table of results of the value of mathematical problem solving abilities on students' learning styles. It can be concluded that the mathematical problem solving abilities of students who have a visual learning style are higher than the mathematical problem solving abilities of students who have audiotorial and kinesthetic learning styles. And the problem solving abilities of students who have an audiotorial learning style are higher than students who have a kinesthetic learning style. Therefore to improve mathematical problem solving abilities, students need better learning styles from 3 types of student learning styles so they can compete with other countries, and can improve rankings better than before. So that the relationship between mathematical problem solving abilities and student learning styles at SMA Negeri 1 Suliki is valid/reliable. Tujuan penelitian ini adalah untuk mengetahui hubungan kemampuan pemecahan masalah matematika dengan gaya belajar siswa. Gaya belajar siswa penting dalam proses pembelajaran dan memahami gaya belajar siswa. Mengenali gaya belajar siswa akan memudahkan untuk memilih kegiatan pembelajaran yang sesuai dan memudahkan siswa dalam menerima informasi. Jenis penelitian ini adalah penelitian kuantitatif. Instrumen yang digunakan adalah soal tes dan angket. Sampel dalam penelitian ini adalah siswa kelas XI SMA Negeri 1 Suliki dengan jumlah siswa 20 orang siswa. Hasil dari penelitian adalah dalam tabel hasil nilai kemampuan pemecahan masalah matematika terhadap gaya belajar siswa dapat disimpulkan bahwa kemampuan pemecahan masalah matematika dengan siswa yang memiliki gaya belajar visual lebih tinggi dibandingkan kemampuan pemecahan masalah matematika siswa yang memiliki gaya belajar audiotorial dan kinestetik. Dan kemampuan pemecahan masalah siswa yang memiliki gaya belajar audiotorial lebih tinggi dari siswa yang mempunyai gaya belajar kinestetik. Maka dari itu untuk meningkatkan kemampuan pemecahan masalah matematika, diperlukan gaya belajar siswa dari 3 jenis gaya belajar siswa yang lebih baik agar bisa dapat bersaing dengan negara lain, dan dapat meningkatkan peringkat yang lebih baik dari sebelumnya. Sehingga hubungan kemampuan pemecahan masalah matematika dengan gaya belajar siswa di SMA Negeri 1 Suliki bersifat valid/reliabel.